The treatment of vulval lichen sclerosus with a very potent topical steroid (clobetasol propionate 0.05%) cream. - Dalziel, K; Millard, P; Wojnarowska, F (1991)
The clinical and histological response to 12 weeks of treatment with a very potent topical fluorinated steroid was studied in 15 patients with vulval lichen sclerosus (LS) who were treated with twice daily applications of clobetasol propionate 0.05% cream (Dermovate, Glaxo U.K.). Thirteen patients completed the study and all showed a marked clinical improvement. Histological measurements of skin biopsies taken before and after treatment showed a significant reduction in the characteristic features of LS. One patient developed contact sensitivity to clobetasol propionate. There was no evidence of infection or skin atrophy during the study. Patients completing the study have been followed up for up to 22 months and have been maintained in remission with moderately potent topical steroids which had previously been ineffective.